Pengaruh Kesadahan Total Pada Desain Formula Lumpur Pemboran - M.Mahlil Nasution; Edy Soesanto; Chesy Meifani (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Research was conducted to analyze the effect of total hardness on the design of optimal drilling mud formulas. Total hardness, which is a measure of the content of dissolved minerals and ions in water, can have a significant impact on the physical and chemical properties of a drilling mud. Factors such as the type of rock formation, water content in the formation, ambient temperature, hydrostatic pressure, and the type of admixture in the mud also influence the design of the mud formula. From the research results, it was found that total hardness can significantly affect the properties of drilling mud. The increase in total hardness tends to affect the rheology of the drilling mud. However, this influence is not linear and can differ depending on the specific conditions and sludge composition. This study provides a better understanding of the relationship between total hardness and drilling mud properties and can be used as a reference in designing optimal mud formulas. Considering the effect of total hardness and other factors, the design of the drilling mud formula can be optimized to meet the requirements of effective and efficient drilling.